L’argentiere romano Filippo Tofani nel Portogallo di Giovanni V (1706-1750): "Con ogni diligenza e perfezione in tutto, e per tutto secondo l’idea dell’autore" - Vale, Teresa Leonor. M. (2015)
In this article we wish to awaken interest in the works realized for Portugal by the Roman silversmith Filippo Tofani (1694-1767) during the reign of Giovanni V "the Magnanimo" (1706-1750) a king who was particularly interested in the up-dating of Portuguese art and culture at the beginning of the 18th century above all in relation to the developments of Roman artistic culture. Only part of Tofani's works have remained but documents found in archives testify the existence of missing works which will receive our attention in the present study. The choice of this artist in this research is due to his importance and that of his works, in a European context, going beyond the Italian and Portuguese confines. Tofani rvas considered " a Professor" by his contemporaries; he was an artist of great importance also for the role he carried out as educator and for his influence on the work of other silversmiths.